2016
DOI: 10.1103/physrevb.94.144419
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic theory of spin relaxation mechanisms in the Landau-Lifshitz-Gilbert equation of spin dynamics

Abstract: Starting from the Dirac-Kohn-Sham equation we derive the relativistic equation of motion of spin angular momentum in a magnetic solid under an external electromagnetic field. This equation of motion can be rewritten in the form of the well-known Landau-Lifshitz-Gilbert equation for a harmonic external magnetic field, and leads to a more general magnetization dynamics equation for a general time-dependent magnetic field. In both cases with an electronic spin-relaxation term which stems from the spin-orbit inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 83 publications
(138 reference statements)
2
106
0
1
Order By: Relevance
“…Thus, a comparison can be made between the Gilbert damping parameter and the magnetic inertia parameter of a pure system. As noticed above, both the parameters are given by the magnetization susceptibility tensor, however it should be noted that the quantiy r α p β is imaginary itself, because [11],…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Thus, a comparison can be made between the Gilbert damping parameter and the magnetic inertia parameter of a pure system. As noticed above, both the parameters are given by the magnetization susceptibility tensor, however it should be noted that the quantiy r α p β is imaginary itself, because [11],…”
Section: Discussionmentioning
confidence: 95%
“…Therefore one has to work together with those terms and cannot only perform the dynamics with an individual term. In an earlier work [11] we have shown that taking an uniform magnetic field along with the gauge A = B×r 2 will preserve the hermiticity. The essence of the uniform field lies in the assumption that the skin depth of the electromagnetic field is longer than the thickness of the thin-film samples used in experiments.…”
Section: Magnetization Dynamicsmentioning
confidence: 96%
See 3 more Smart Citations